Liberia : The Violence of Democracy - Moran, Mary H., 1957- (Ethnography of political violence., 2006)
This book argues that democracy is not a foreign import into Africa, but that essential aspects of what we in the West consider democratic values are part of the indigenous African traditions of legitimacy and political process. In the case of Liberia, these democratic traditions include institutionalized checks and balances operating at the local level that allow for the voices of structural subordinates (women and younger men) to be heard and be effective in making claims. Mary H. Moran argues that the violence and state collapse that have beset Liberia and the surrounding region in the past two decades cannot be attributed to ancient tribal hatreds or neopatrimonial leaders who are simply a modern version of traditional chiefs. Rather, democracy and violence are intersecting themes in Liberian history that have manifested themselves in numerous contexts over the years."--Book jacket.